Expression of Castanea crenata Allene Oxide Synthase in Arabidopsis Improves the Defense to Phytophthora cinnamomi - Serrazina, Susana; Machado, Helena; Costa, Rita Lourenço; Duque, Paula; Malhó, Rui (Frontiers in Plant Science, 2021)
Allene oxide synthase (AOS) is a key enzyme of the jasmonic acid (JA) signaling pathway. The AOS gene was previously found to be upregulated in an Asian chestnut species resistant to infection by the oomycete Phytophthora cinnamomi (Castanea crenata), while lower expression values were detected in the susceptible European chestnut (Castanea sativa). Here, we report a genetic and functional characterization of the C. crenata AOS (CcAOS) upon its heterologous gene expression in a susceptible ecotype of Arabidopsis thaliana, which contains a single AOS gene. It was found that Arabidopsis plants expressing CcAOS delay pathogen progression and exhibit more vigorous growth in its presence. They also show upregulation of jasmonic acid and salicylic acid-related genes. As in its native species, heterologous CcAOS localized to plastids, as revealed by confocal imaging of the CcAOS-eGFP fusion protein in transgenic Arabidopsis roots. This observation was confirmed upon transient expression in Nicotiana benthamiana leaf epidermal cells. To further confirm a specific role of CcAOS in the defense mechanism against the pathogen, we performed crosses between transgenic CcAOS plants and an infertile Arabidopsis AOS knockout mutant line. It was found that plants expressing CcAOS exhibit normal growth, remain infertile but are significantly more tolerant to the pathogen than wild type plants. Together, our results indicate that CcAOS is an important player in plant defense responses against oomycete infection and that its expression in susceptible varieties may be a valuable tool to mitigate biotic stress responses.